2018
DOI: 10.4172/1758-4272.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for granulomatous lymphocytic interstitial lung disease in a patient with common variable immunodeficiency. Is single therapy enough?

Abstract: Keywords: common variable immunodeficiency • granulomatous lymphocytic interstitial lung disease • autoimmune hemolytic anemia • idiopathic thrombocytopenic purpura • pulmonary function tests Abstract: Granulomatous Lymphocytic Interstitial Lung Disease (GLILD) is an inflammatory pulmonary complication of common variable immunodeficiency (CVID) with distinctive patterns in the biopsy; Granulomatous Disease, Lymphocytic Interstitial Disease, Follicular Bronchiolitis and Organizing Pneumonitis. Without the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Pulmonary function tests (PFT) as assessment tools were reported in 40 studies ( 5 , 13 , 15 18 , 20 24 , 27 , 28 , 30 36 , 38 45 , 49 , 52 54 , 56 , 57 , 59 , 60 , 62 64 , 69 ), and included spirometry, measurement of diffusion capacity and assessment of static lung volumes (i.e., total lung capacity (TLC), and residual volume (RV)). Two studies reported PFT abnormalities as potential diagnostic criteria for CVID-ILD in addition to CT ( 64 , 65 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pulmonary function tests (PFT) as assessment tools were reported in 40 studies ( 5 , 13 , 15 18 , 20 24 , 27 , 28 , 30 36 , 38 45 , 49 , 52 54 , 56 , 57 , 59 , 60 , 62 64 , 69 ), and included spirometry, measurement of diffusion capacity and assessment of static lung volumes (i.e., total lung capacity (TLC), and residual volume (RV)). Two studies reported PFT abnormalities as potential diagnostic criteria for CVID-ILD in addition to CT ( 64 , 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most common diagnostic findings were non-necrotizing granulomatous and lymphocytic inflammation. The use of video-assisted thoracoscopic surgery (VATS) was reported in 17 studies ( 15 , 16 , 21 , 26 , 33 , 34 , 36 , 39 41 , 45 , 47 , 57 , 60 , 62 , 63 , 69 ). The results from 81 patients demonstrated the characteristic histological findings of CVID-ILD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All described treatment courses of rituximab monotherapy for CVID+PGD were effective ( Table 6). In 20 of the 22 patients with CVID+PGD were rituximab was part of treatment regimen, granulomatous disease was only present in the lungs (Supplemental Table 4) (49,(59)(60)(61)(62)(63)(64)(66)(67)(68)(69). In the majority of the included cases the dose of rituximab as part of combination therapy with azathioprine was consistent, namely 375 mg/m2 (49,59,60,62).…”
Section: Rituximab With or Without Azathioprinementioning
confidence: 99%